1999
DOI: 10.1016/s0896-6273(00)81127-7
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Emergence and Progression of a Tauopathy in Transgenic Mice Overexpressing the Shortest Human Tau Isoform

Abstract: Filamentous tau aggregates are hallmarks of tauopathies, e.g., frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17) and amyotrophic lateral sclerosis/parkinsonism-dementia complex (ALS/PDC). Since FTDP-17 tau gene mutations alter levels/functions of tau, we overexpressed the smallest human tau isoform in the CNS of transgenic (Tg) mice to model tauopathies. These mice acquired age-dependent CNS pathology similarto FTDP-17 and ALS/PDC, including insoluble, hyperphosphorylated tau and argy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
412
3
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(449 citation statements)
references
References 45 publications
31
412
3
3
Order By: Relevance
“…Treatment with paclitaxel restores fast axonal transport in spinal axons, increases axonal MTs, and ameliorates motor impairments in tau transgenic mice that developed filamentous tau inclusions (mostly in the spinal cord) (Ishihara et al 1999(Ishihara et al , 2001Zhang et al 2005). Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with paclitaxel restores fast axonal transport in spinal axons, increases axonal MTs, and ameliorates motor impairments in tau transgenic mice that developed filamentous tau inclusions (mostly in the spinal cord) (Ishihara et al 1999(Ishihara et al , 2001Zhang et al 2005). Paclitaxel also blocks Aβ-induced phosphorylation of tau by preventing the cleavage of p35 by calpain (Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…40 -45 They have tau immunoreactivity in neurons and their processes, but only one study has demonstrated immunolabeling of astrocyte-like cells at the light microscopic level. 42 Another study 43 showed aggregates of 10-to 20-nm straight filaments in myelinated spinal cord axons. The filaments were immunolabeled by antibodies to tau, tubulin, and neurofilaments.…”
Section: Discussionmentioning
confidence: 99%
“…In tissue culture, phosphorylation of tau repeats resulted in transport impairment, and deficits in fast anterograde transport were described in tau transgenic mice. 27,220 One major advantage of microtubule-stabilizing strategies is the availability of approved and well-established chemotherapeutic drugs such as taxol. Taxol and its derivative taxane analog TX67 stabilize microtubules and promote tubulin polymerization.…”
Section: Microtubule-stabilizing Drugsmentioning
confidence: 99%